Escape rooms in Poland: A demand-led approach using ‘netnographic’ research - Stasiak, Andrzej (Turyzm/Tourism, 2019)
During five years of extremely rapid and spontaneous development, escape rooms have become a permanent component of Polish urban space. At the same time, this form of recreation has gained a whole community of enthusiasts. The aim of the article is to present a comprehensive description of the people who visit escape rooms in Poland through an online survey including 718 users of lockme.pl, the largest promotional and booking portal in the country. The results have enabled the author to identify the socio-demographic features of the players, sources of information about escape rooms, user motivations, the frequency, character and course of visits, the emotions accompanying the game, as well as general opinions and evaluations of Polish escape rooms.